2023
DOI: 10.3389/fpls.2022.1048656
|View full text |Cite
|
Sign up to set email alerts
|

Convergent evolution of the annual life history syndrome from perennial ancestors

Abstract: Despite most angiosperms being perennial, once-flowering annuals have evolved multiple times independently, making life history traits among the most labile trait syndromes in flowering plants. Much research has focused on discerning the adaptive forces driving the evolution of annual species, and in pinpointing traits that distinguish them from perennials. By contrast, little is known about how ‘annual traits’ evolve, and whether the same traits and genes have evolved in parallel to affect independent origins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 160 publications
0
5
0
Order By: Relevance
“…Various investigations have shown that unfavorable environmental stressors, including light deprivation, lead to rapid leaf senescence [ 34 ]. The understanding of darkness- or age-induced senescence is of high economic relevance as senescence can significantly decrease the post-harvest shelf-life of a plant as well as lead to yield loss in agriculture [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Various investigations have shown that unfavorable environmental stressors, including light deprivation, lead to rapid leaf senescence [ 34 ]. The understanding of darkness- or age-induced senescence is of high economic relevance as senescence can significantly decrease the post-harvest shelf-life of a plant as well as lead to yield loss in agriculture [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Annual Z. marina plants typically have limited rhizome development and allocate most of the aboveground biomass to reproductive shoots [ 7 ]. Such differential allocation to vegetative and reproductive structures has been found for terrestrial angiosperms when comparing annual and perennial congeneric species [ 4 , 15 , 16 ].…”
Section: Seed Production Is Higher In Annual Than Perennial Populationsmentioning
confidence: 88%
“…Assuming that there is a trade-off between vegetative (clonal) growth and sexual reproduction [ 16 , 17 , 18 ] and that sexual reproduction competes with the vegetative functions for necessary resources for plant growth and maintenance, an annual life cycle should only be favored over a perennial cycle when the survivorship of the established plant is lower than that of the seed or seedling. Such unfavorable conditions for vegetative development may recur periodically (often seasonally) or at stochastic intervals in highly unpredictable environments [ 19 ].…”
Section: Annual Populations Live In More Stressful Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA quanti cation, especially by ow cytometry, which is well established as a reliable and accurate method, provides a time-saving and e cient way to study such differentiation processes at different scales, from variation within populations to large areas of distribution (Paule et Bureš et al 2024). In addition to the saltational changes caused by polyploidization, gradual, more or less continuous changes in genome size can also be detected, sometimes even between populations or closely related taxa, which typically result primarily from the ampli cation of mobile elements in the genome and their gradual loss over longer periods of time, leading to genome enlargement or reduction (Zedek et Many genera of Pooideae show a strong proliferation of annual species, a well-known process of angiosperm life form evolution (Hjertaas et al 2023) that is often associated with changes in genome size (Bennett and Leitch 2005; Knight et al 2005; Leitch and Bennett 2007). However, the Pooideae are not only characterized by many annuals in Mediterranean-type climates, but also by particularly coldadapted species in the boreal to Arctic, and sub-Antarctic to Antarctic regions, including one of only two native owering plant species of Antarctica, Deschampsia antarctica (Greene and Holtom 1971).…”
Section: Introductionmentioning
confidence: 99%